A rare case of brain metastasis - Gupta, VIjay Kumar; Basantani, Neeraj; Carvalho, A S; Gupta, Ekata; Goyal, Nitesh Kumar (Nepal Journal of Neuroscience, 2020)
Head and neck squamous cell carcinoma metastasis to brain is unusual and rare. We present a case of a 61-year-old man with a primary oral squamous cell carcinoma who was referred to our department for evaluation of decreased sensorium and hemiparesis. Magnetic resonance imaging of the brain revealed a ring enhancing central hypo-intense lesion with surrounding perilesional oedema on T1WI in the left frontal lobe. Left frontal craniotomy with gross total tumour removal was performed. Histopathological examination confirmed metastatic squamous cell carcinoma. The patient was subsequently offered adjuvant radiation therapy. To the best of our knowledge, few such cases have been reported.